Sudden death due to diabetic ketoacidosis following power failure of an insulin pump: Autopsy and pump data. (April 2019) - Kjærulff, Mette Louise Blouner Gram; Astrup, Birgitte Schmidt
Abstract: Purpose: To report a case in which autopsy findings and data from an insulin pump illustrate the course up to the death of a 31-year-old man with a history of type 1 diabetes mellitus who was found dead in his apartment with his insulin pump disassembled and placed in another room. Methods: Autopsy findings including histological, toxicological and biochemical examination are presented. Postmortem download of data from the insulin pump gave the history of the pump, which included blood glucose, insulin bolus, carbohydrate intake and the time course in the days to death, and the pump settings were recorded. For this case report, police reports on the death as well as hospital records were also reviewed. Results: At the patch for the insulin pump, nothing abnormal was found. Biochemical analysis showed glucose of 35 mmoL/L in vitreous humor fluid indicating antemortem hyperglycemia, and ketone bodies in the blood of 11.0 mmoL/L indicating ketoacidosis. Acute pulmonary hemostasis, chronic fat accumulation in the liver and acute fat accumulation in the kidneys were histological detected. There were no signs of late diabetic complications such as nephropathy or cardiovascular disease in the tissues. Insulin pump data showed that after three alarms, a power failure of the pump occurred leading to discontinuing insulin delivery, and about 48 h before the deceased was found dead, his body was depleted of insulin. Conclusion: The cause of death is believed to be diabetic ketoacidosis due to completely lack of insulin because of power failure of the insulin pump, which therefore has been a decisive factor in the cascade of events that led to death. The case is, to our knowledge, the first to illustrate a death caused by diabetic ketoacidosis which is supported by autopsy findings and by data of an insulin pump up to the time of power failure. It is a strong example of usefulness of postmortem download of data from insulin pumps to help determine the cause of death among diabetics. Forensic pathologists should therefore review data and history of the pump systematically. Highlights: Analysis showed high glucose in vitreous humor fluid and ketone bodies in the blood. Pump data showed power failure leading to discontinuation of insulin delivery. Results indicated that diabetic ketoacidosis was the cause of death. Insulin pump data provided additional information of what triggered death. The case is a strong example of usefulness of postmortem download of pump data.